Assessment of the impact of the economic factors on stock prices: cross-sectoral approach - Macenaite, Joana; Keliuotyte-Staniuleniene, Greta (Technium Social Sciences Journal, 2023)
This paper analyses the impact of economic factors on stock prices based on a cross-sectoral approach. After the analysis of academic literature in the field, the graphical analysis of stock price movements in different sectors is conducted and multiple stock price factors panel regression models are constructed. The results of the research show that the strongest difference between sectors was observed in the effect on stock prices of such factors as inflation and interest rates. When analyzing other factors, no significant difference in effect between sectors was observed.